2014
DOI: 10.1002/esp.3592
|View full text |Cite
|
Sign up to set email alerts
|

Reduced bed material stability and increased bedload transport caused by foraging fish: a flume study with juvenile Barbel (Barbus barbus)

Abstract: The plants and animals that inhabit river channels may act as zoogeomorphic agents affecting the nature and rates of sediment recruitment, transport and deposition. The impact of benthic‐feeding fish, which disturb bed material sediments during their search for food, has received very little attention, even though benthic feeding species are widespread in rivers and may collectively expend significant amounts of energy foraging across the bed. An ex situ experiment was conducted to investigate the impact of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(73 citation statements)
references
References 90 publications
4
67
2
Order By: Relevance
“…The protocol pertaining to fish husbandry was consistent with that described in Pledger et al (2014Pledger et al ( , p. 1501, with two modifications. First, water in two 1000-l holding tanks was cooled and maintained at a constant temperature of 16.70°C ± 0.003 (±1 standard deviation).…”
Section: Fish Husbandrymentioning
confidence: 97%
See 4 more Smart Citations
“…The protocol pertaining to fish husbandry was consistent with that described in Pledger et al (2014Pledger et al ( , p. 1501, with two modifications. First, water in two 1000-l holding tanks was cooled and maintained at a constant temperature of 16.70°C ± 0.003 (±1 standard deviation).…”
Section: Fish Husbandrymentioning
confidence: 97%
“…These findings emphasise the role of biotic factors in controlling geomorphic impact. Third, Pledger et al (2014) found that foraging juvenile Barbel modified water-worked surface gravels, undoing stable imbricate structures and increasing microtopographic roughness. These changes coincided with an average increase in initial bedload flux and overall sediment yield of 60% and 82%, respectively, under entrainment flows.…”
Section: ; and Other Benthic Feeders Such As Bream Abramis Brama Tenmentioning
confidence: 98%
See 3 more Smart Citations